(untitled) (Communications in Computational Physics, 2024)
In this paper, an improved diffuse-interface lattice Boltzmann method for particulate flows is developed. In this method, the difference in viscosity between the fluid and the particle is considered, and a smooth function is introduced to the collision term of the evolution equation. Some simulations are performed to test the method, and the numerical results show that, compared to the previous diffusion-interface lattice Boltzmann method [J. Liu et al., Comput. Fluids 233 (2022) 105240] which only has a first-order accuracy in space, the present one has a second-order convergence rate in space.